Competition Panels and Diagrams. Construction and Design Manual. - Hossbach, Benjamin; Lehmhaus, Christian; Eichelmann, Christine (DOM Publ., 2016)
Architectural competitions act as a tool for enhancing a design and selecting planning partners. The quality of urban development, high-rise buildings and open spaces is thus sustainably improved. Nevertheless, this planning and awarding tool is repeatedly scrutinised. Twenty-five international projects from 2009 to 2015 presented in this volume shed light on design methods and techniques employed by internationally renowned architects. The collection is supplemented by explanations of technical and formal criteria regarding the presentation of competition entries and addresses expenditure issues in relation to prize money and architects fees. This manual not only includes an essay on the history of architectural drawings submitted in competitions, but also presents theses and guest contributions by judges and entrants. These address the importance of competition designs in relation to panels and diagrams since these hold significant sway over the eventual outcome.
Keywords: Methode; Architekturwettbewerb; Städtebaulicher Wettbewerb; Wettbewerbsentwurf; Architektur; Entwurf; Bauprojekt; Planungshilfe; Beispielsammlung; Städtebauwettbewerb; Entwerfen; Präsentation; Handbuch